2048. Molecular Characterization and Resistance Factors of Circulating Acinetobacter baumannii isolates in South-East Michigan. (15th December 2022) - Choi, Hosoon; Xu, Jing; Hwang, Munok; Jinadatha, Chetan; Navarathna, Thanuri; Ashby, Landon; Bennett, Morgan; Kaye, Keith S; Dhar, Sorabh; Chatterjee, Piyali
Abstract: Background: Carbapenem-resistant Acinetobacter baumannii ( CRAb ) is increasing due to widespread use of antibiotics. Multidrug resistant (MDR) CRAb is a major threat to public health as treatment options are limited. The objective of this study is to elucidate the molecular epidemiology of circulating antibiotic resistance genes causing MDR CRAb infections by using a combination of whole-genome M ulti-L ocus S equence T yping (wgMLST) and antibiotic susceptibility phenotyping. Table 1. Molecular characterization of MDR CRAb isolates *The numbers indicate % of sequence identity match for each Beta-lactamase gene. Methods: Bacterial isolates were derived from cultures taken from subjects 48 hours following admission as part of routine clinical care for patients between 2017-2020. Isolates were obtained from 16 hospital units (both ICU and non-ICU) across two hospitals in the Detroit area. Whole Genome Sequencing (WGS) was performed using Illumina MiniSeq or Nextseq. WgMLST analysis was performed using BioNumerics software v7.6. ResFinder software was used for analysis of antibiotic resistance genes. Isolates underwent antibiotic susceptibility testing using a broth microdilution method (VITEK2) and Clinical & Laboratory Standards Institute (CLSI) minimum inhibitory concentration (MIC) cut offs. Results: Out of the 95 total isolates, 51(54%) were CRAb isolates and of the CRAb isolates, 21(41%) were MDR CRAb . WgMLST identified that majority of the circulating MDR CRAb isolates belonged to ST2 Pas (ST195 Ox and ST208 Ox ) based on CDC definitions (Table 1). MDR CRAb isolates were resistant to 3 different classes of antibiotics including aminoglycosides, fluroquinolones and β-lactams. β-lactamase genes present include (blaADC-25, blaOXA-23, blaOXA-66 and blaTEM1D) for both ST195 Ox and ST208 Ox and (blaADC-25, blaOXA-23 and blaOXA-223) for ST406 Pas (ST310 Ox ). Among the patients with MDR CRAb infections, most were males with respiratory infections in a non-ICU setting. Conclusion: The study demonstrated a high proportion of isolates belonged to ST2 Pas carrying multiple beta-lactamase genes including blaOXA-23 gene. ST406 Pas might be an emerging lineage carrying the blaOXA-23 gene. In addition to stringent infection control measures, continuous surveillance is recommended in limiting the spread of MDR CRAb isolates in the healthcare settings. Disclosures: Chetan Jinadatha, MD, MPH, AHRQ R01 Grant-5R01HS025598: Grant/Research Support|EOS Surfaces: Copper Coupons and materials for testing Keith S. Kaye, MD, MPH, Allecra: Advisor/Consultant|GlaxoSmithKline plc.: Receiving symposia honoraria|GlaxoSmithKline plc.: GlaxoSmithKline plc.-sponsored study 212502|Merck: Advisor/Consultant|qpex: Advisor/Consultant|Shionogi: Grant/Research Support|Spero: Advisor/Consultant Piyali Chatterjee, PhD, AHRQ Grant # 1R03HS027667-01: Grant/Research Support|AHRQ Grant # 1R03HS027667-01: Central Texas Veterans Health Care System.